Gamification for sales incentives - Jacek Woźniak (Contemporary Economics, 2020)
Gamification as the use of game mechanisms for motivation in non-game contexts has been gaining popularity and is considered one of the hottest topics in management. However, there is little research on gamification in remuneration systems, especially with regard to the sales force. The article discusses some problems posed by different types of incentives schemes for sales persons as well as two approaches that could be used for gamification in this area; the so called BLAP approach to gamification and gamification based on prize drawing. The results of two questionnaire-based opinion studies carried out on two groups of about 100 sales representatives show that the experience and knowledge in the area of gamification is low in this group of employees. Acceptance of gamification was studied taking into consideration institutional (i.e., the sales cycle length), organizational (i.e., satisfaction from the existing bonus scheme), psychological (i.e., risk adverseness), and situational (i.e., the need for high regular income) factors. Both bonus draws among sales representatives who achieved targets and collecting points exchangeable for non-material rewards are accepted by some of traders, and such acceptance of either of the two types of gamification is correlated with a dissatisfaction with the existing bonus scheme.
Keywords: J28; J29; J31; J33; M12; M52; 330; gamification; sales force; compensation; incentives for sales force; gamification in sales force management